Experience in Using Low-Dose Computed Tomography in Children and Adolescents with Pulmonary Tuberculosis - I. Yu. Petrakova; S. G. Mikhaylov; I. Е. Tyurin; M. F. Gubkina; M. Yu. Izmaylov (Вестник рентгенологии и радиологии)
Objective: to assess the possibilities of using low-dose computed tomography (LDCT) in children and adolescents with pulmonary tuberculosis (TB).Material and methods. The design of the study, which included patients aged 2–17 years with active pulmonary TB and post-TB changes treated in Central Tuberculosis Research Institute in 2021–2023, consisted of two parts as follows: part 1 (a prospective selective study) – independent assessment of LDCT vs standard-dose CT (SDCT) diagnostic accuracy by two radiologists in 44 patients with TB process stabilization; part 2 – cohort one-time assessment of LDCT image quality in 144 patients at different phases of TB treatment. LDCT was performed on the Somatom Emotion 16 CT scanner (Siemens, Germany) by filtered backprojection algorithm; SDCT was conducted on the Somatom go.Up CT scanner by iterative reconstruction algorithm. In patients aged 2–12 years, pediatric protocols, and in patients aged 13–17, standard protocols were used. Radiation exposure was evaluated considering the effective dose (ED).Results. In patients aged 13–17 years, the noise level was lower and the signal-to-noise ratio was higher with LDCT for all anatomical structures, with the exception of pulmonary parenchyma. In patients aged 2–12 years, the signal-to-noise ratio was the same or slightly higher in SDCT. In the subjective assessment, good image quality was noted with a high correlation between the assessments of radiologists. ED was 2.17 times lower for LDCT than for SDCT in adolescents and 1.91 times lower in children. In patients aged 2–3 years, the quality essentially depended on their immobility during the procedure, though under sedation it was good in 92% of cases.Conclusion. In conditions of sufficient immobility of the patient, LDCT provided good image quality of tuberculous changes with a decrease in ED compared to SDCT by 2.17 times in adolescents and by 1.91 times in children.